2020
DOI: 10.1002/mds.28335
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy for Parkinson's Disease: A Systematic Review and Meta‐Analysis

Abstract: Background Electroconvulsive therapy (ECT) is a well‐established treatment for psychiatric disorders, including depression and psychosis. ECT has been reported to be effective in treating such psychiatric symptoms in patients with Parkinson's disease (PD) and has been also reported to be effective in treating motor symptoms. The aim of the study is to summarize previous clinical studies investigating the efficacy of ECT for symptoms in patients with PD. Methods A systematic review and meta‐analysis of any stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 47 publications
4
50
1
7
Order By: Relevance
“…They also demonstrated that ECT did not decrease cognitive functioning, and decreased the 'wearing-off' phenomenon associated with levodopa. 48 Borisovskaya et al also conducted a meta-analysis of 116 case reports, which supported Takamiya's findings. 49 Despite the conclusions from these studies, ECT is not readily given as treatment, seemingly due to stigma, patient hesitancy and the transient confusion and delirium that occur in up to 33% of patients with PD who undergo ECT.…”
Section: Treatment Approaches For Depression In Parkinson's Diseasementioning
confidence: 59%
“…They also demonstrated that ECT did not decrease cognitive functioning, and decreased the 'wearing-off' phenomenon associated with levodopa. 48 Borisovskaya et al also conducted a meta-analysis of 116 case reports, which supported Takamiya's findings. 49 Despite the conclusions from these studies, ECT is not readily given as treatment, seemingly due to stigma, patient hesitancy and the transient confusion and delirium that occur in up to 33% of patients with PD who undergo ECT.…”
Section: Treatment Approaches For Depression In Parkinson's Diseasementioning
confidence: 59%
“…These remarkable efficacy data of ECT were mainly found in the predominant indication of therapy-resistant depression and have stimulated ECT to be used successfully in a variety of mental and neurological disorders such as first-episode schizophrenia ( Grover et al, 2019 ), acute mania ( Zhang et al, 2021 ), during the early stages of antidepressive treatment ( Haq et al, 2015 ; van Diermen et al, 2018 ), for motor and behavioral symptoms of Parkinson’s disease ( Takamiya et al, 2021 ), and for sustaining mood improvement in geriatric depression ( Kellner et al, 2016 ). Furthermore, ECT is particularly effective in patients with depression, including psychotic features and elderly people with depression ( van Diermen et al, 2018 ), to be beneficial as an augmenting strategy in treatment-resistant schizophrenia ( Grover et al, 2019 ; Sinclair et al, 2019 ; Chiu et al, 2020 ) with maintenance ECT providing an effective form of relapse prevention ( Ward et al, 2018 ), in mania ( Elias et al, 2021 ), catatonia ( Kellner et al, 2020 ), severe agitation ( Grover et al, 2019 ), specific mental disorders in multiple sclerosis ( Yahya and Khawaja, 2021 ), and prepartum and postpartum psychotic states ( Gazdag et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…67 A more recent meta-analysis by Takamiya et al corroborated these findings, revealing a statistically significant effect size of ECT on depression in PD patients with improvement of motor symptoms in patients both with and without psychiatric symptoms. 68 In spite of its apparent efficacy, ECT remains a scarcely used treatment modality for PD-related depression. Aversion to ECT appears to be multifactorial; contributing factors likely include the persistent stigma surrounding ECT, the inability to predict individual treatment outcomes with correspondingly variable need for maintenance ECT, and intolerability to the transient side effects (e.g., confusion, delirium) that occur in up to a third of PD patients.…”
Section: Treatment Of Mood Disorders In Parkinson’s Diseasementioning
confidence: 99%
“…66,67 The fear of impaired neurocognitive function after ECT may also contribute to the paucity of ECT use, although this is an uncommon consequence of ECT in PD patients. 67 -69…”
Section: Treatment Of Mood Disorders In Parkinson’s Diseasementioning
confidence: 99%